Axial behavior of FRP confined low-strength concrete with polyurea. (December 2020) - Akın, Emre; Tunaboyu, Onur; Avşar, Özgür
Abstract: The use of fiber-reinforced polymer (FRP) composites for the confinement of concrete has become one of the major retrofitting methods for improving the axial behavior of reinforced concrete columns. Although a significant improvement in the axial behavior of concrete could be obtained by FRP confinement, the retrofitting material may not be utilized up to its ultimate strain capacity due to stress concentrations caused by the deformed concrete or irregularities of the concrete surface. The study aims to increase the effectiveness of FRP confinement by a polyurea coating that is provided between the concrete and FRP. For this purpose, monotonic and cyclic axial compression tests were conducted on twenty-eight specimens with low-strength concrete, which is very common in substandard reinforced concrete buildings. The test results indicate a more uniform stress distribution on the confining material resulting in an increased ultimate strain capacity with the provided polyurea coating. Improvement in the effectiveness of FRP confinement by means of polyurea is more pronounced in the cyclic tests.